Epidemiology and the economic burden of traumatic fractures in China: A population-based study - Huang, Bo-xuan; Wang, Yan-hua; Wang, Hai-bo; Wang, Chu; Jin, Fei-fei; Li, Jing; Gan, Lan-xia; Shi, Ying; Jiang, Bao-guo; Zhang, Dian-ying (Frontiers in Endocrinology, 2023)
Objectives National data on the admission rate, distribution, in-hospital mortality, and economic burden of traumatic fractures in China is unclear. We aimed to conduct a cross-sectional population-based study to determine such above data at the national level in China. Methods A national administrative database was used to review all traumatic fracture hospitalizations in China during 2020, from which a total of 2,025,169 inpatients with traumatic fractures was retrieved. Admission rates and in-hospital mortality rates stratified by age, sex, and region were calculated. The causes of traumatic fracture and economic burden were described. Results The admission rate of traumatic fractures of all China population in 2020 was 1.437‰. The admission rate increased with age and varied with genders and causes of injuries. Falls are the leading cause of traumatic fracture hospitalization, followed by road traffic injuries. The most common diagnoses were femoral neck fractures, with a number of 138,377. The in-hospital mortality was 1.209‰. Road traffic injuries led to the highest in-hospital mortality. The median length of stay was 10 days, with the median hospitalization cost of ¥20,900 (about 3,056). Conclusion Traumatic fractures are concerning conditions with a high admission rate and in-hospital mortality in China, which are mainly caused by falls and road traffic injuries. The government should implement more public health policies to enhance the health of the elderly and improve transportation safety to prevent traumatic fractures.